2008
DOI: 10.4049/jimmunol.180.12.8400
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of TLR2 Expression by Prostaglandins in Brain Glia

Abstract: TLR have emerged as important primary sensors for diverse stimuli and are increasingly implicated in various diseases. However, the molecular mechanisms underlying the regulation of the TLR system remain poorly understood. In this study, we report that some PGs may control TLR-mediated inflammatory events through modulation of TLR2 expression in brain immune cells. We first found that 15-deoxy-Δ12,14-PG J2 (15d-PGJ2) markedly altered the expression of TLR2 but not TLR4, TLR1, and TLR9 at the message and protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 76 publications
3
22
0
Order By: Relevance
“…The evidence that IVD degeneration and low back pain are correlated with increased levels of pro-inflammatory cytokines is increasing . Inflammatory processes are regulated, for example, by toll-like receptors (TLRs), which are primarily expressed on the immune cells as a first line of host defence, but have also been detected in the other cell types, including IVD cells Yoon et al, 2008). Recently, our group confirmed basal expression of TLRs in IVD cells and showed that expression of TLR2, 4 and 6 is increased during IVD degeneration (Klawitter et al, 2014), thus further underlying the clinical relevance of inhibiting IVD inflammation.…”
Section: Discussionmentioning
confidence: 78%
“…The evidence that IVD degeneration and low back pain are correlated with increased levels of pro-inflammatory cytokines is increasing . Inflammatory processes are regulated, for example, by toll-like receptors (TLRs), which are primarily expressed on the immune cells as a first line of host defence, but have also been detected in the other cell types, including IVD cells Yoon et al, 2008). Recently, our group confirmed basal expression of TLRs in IVD cells and showed that expression of TLR2, 4 and 6 is increased during IVD degeneration (Klawitter et al, 2014), thus further underlying the clinical relevance of inhibiting IVD inflammation.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have shown that TLR expression can be regulated in a stimulus-dependant and cell-type specific manner (Iwasaki and Medzhitov, 2004; Muzio et al, 2000; Visintin et al, 2001; Yoon et al, 2008). IL-1β administration is often used as a model of apoptotic cell death despite controversial reports (Allan, 2002; Cai et al, 2004; Holmin and Mathiesen, 2000; Iwasaki and Medzhitov, 2004; Loddick and Rothwell, 1996; Muzio et al, 2000; Patel et al, 2003; Visintin et al, 2001; Yoon et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies using primary culture of microglia from mouse and human brain tissues revealed mRNA expression of TLR1-9, of which TLR2 and 3 showed the highest level of expression (Bsibsi et al, 2002;Jack et al, 2005;Olson and Miller, 2004). Of the nine TLRs, protein expression has been demonstrated for TLR2, 3, 4, 6, 7 and 9 in primary microglia culture from mouse brain and TLR 1 -4 from human brain (Olson and Miller, 2004;Yoon et al, 2008) (Table 2). In vivo, the expression levels of microglial TLRs seem to be kept low under normal conditions (Bsibsi et al, 2002;Casula et al, 2011;Shi et al, 2011;Zhang et al, 2013;Zhao et al, 2015).…”
Section: Expression Of Tlrs In Microgliamentioning
confidence: 91%
“…PNS neuron rodents TLR3, 4, 5 7, RAGE (in vitro) TLR3,4,5,7,9, RAGE (in vitro) (Allette et al, 2014;Goethals et al, 2010;Park et al, 2014;Qi et al, 2011;Saleh et al, 2013) TLR3, 4, 5, 7, RAGE a (in vivo) (Allette et al, 2014;Barajon et al, 2009;Juranek et al, 2013;Rong et al, 2004a;Saleh et al, 2013;Shibasaki et al, 2010;Vincent et al, 2007) human TLR3, 7, 9 (in vitro) (Qi et al, 2011) RAGE a (in vivo) TLR4 a , RAGE a (in vivo) (Bierhaus et al, 2004;Sousa et al, 2001;Wadachi and Hargreaves, 2006) Schwann cell rodents TLR1-9 (in vitro) TLR3, 4, RAGE (in vitro) (Colomar et al, 2003;Goethals et al, 2010;Lee et al, 2007;Perrone et al, 2008) RAGE a (in vivo) (Shibasaki et al, 2010) human TLR2 (in vitro) (Oliveira et al, 2003) TLR2 a , RAGE a (in vivo) (Oliveira et al, 2003;Sousa et al, 2001) microglia rodents TLR1-9, RAGE (in vitro) TLR2, 3, 4, 6, 7, 9, RAGE (in vitro) (Alarcon et al, 2005;Butchi et al, 2010;DukicStefanovic et al, 2003;Jiang et al, 2014;Kielian et al, 2002;Lehnardt et al, 2003;Olson and Miller, 2004;Pan et al, 2011;…”
mentioning
confidence: 96%